2001
DOI: 10.1074/jbc.m104670200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biological Characterization of Chromofungin, the Antifungal Chromogranin A-(47–66)-derived Peptide

Abstract: In order to examine thoroughly the antifungal activity of chromofungin, confocal laser microscopy was used to demonstrate the ability of the rhodamine-labeled peptide to interact with the fungal cell wall, to cross the plasma membrane, and to accumulate in Aspergillus fumigatus, Alternaria brassicola, and Candida albicans. Our present data reveal that chromofungin inhibits calcineurin activity, extending a previous observation that the N-terminal region of chromogranin A interacts with calmodulin in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 58 publications
(90 reference statements)
2
69
0
Order By: Relevance
“…Research has demonstrated that the C-terminal moiety of bovine vasostatin-1 has potent antifungal activity. The disulfide bridge loop of Cys 17 -Cys 38 in vasostatin-1 was crucial for its antibacterial activity but not necessary for its antifungal activity (19). To further explore the antifungal activity of the vasostatin-1 derived peptide and avoid aggregation, CGA-N46 which corresponded to human CGA residues 31-76 was synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that the C-terminal moiety of bovine vasostatin-1 has potent antifungal activity. The disulfide bridge loop of Cys 17 -Cys 38 in vasostatin-1 was crucial for its antibacterial activity but not necessary for its antifungal activity (19). To further explore the antifungal activity of the vasostatin-1 derived peptide and avoid aggregation, CGA-N46 which corresponded to human CGA residues 31-76 was synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…The Pro-adhesive Site Is Distinct from the Anti-adhesive Site-Previous studies suggested that region 47-66 adopts a helical structure (28). Moreover, other studies showed that the 5A8 epitope (RHQNL) includes residues critical for antibody binding (Arg 53 , His 54 , and Leu 57 ) and residues that are less important (Gln 55 and Asn 56 ), the latter being replaced with alanine without loss of binding (32).…”
Section: Cga Inhibits Fibroblast Adhesion and Spreading-we Havementioning
confidence: 99%
“…In addition, it has been shown that chromofungin can inhibit calcineurin, a calmodulin-activated phosphatase (28). Whether the pro-adhesive activity of (STA)1-78 and 48 -68(Y) requires internalization and inhibition of calmodulin-dependent enzymes or not remains to be investigated.…”
Section: -51 (Rilsi)mentioning
confidence: 99%
See 2 more Smart Citations